Liberating Namibia the long diplomatic struggle between the United Nations and South Africa - Udogu, Emmanuel Ike (McFarland & Co., 2012)
"Offers an in-depth analysis of the political and diplomatic efforts by representatives of the UN, Namibia, and South Africa--assisted by international community, OAU, and Western powers--during struggle for self-rule in Namibia, 1920-1990. This example of conflict resolution technique in global/African studies provides a useful template for conflict negotiation around the world"--Provided by publisher.